2006
DOI: 10.1149/1.2195656
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on Issues Toward 450 mm Wafer

Abstract: This reports a present status of recent technical discussions on 450mm wafer. Discussions are focusing on mechanical wafer specification, especially, wafer thickness based on thermal stress and other factors, which may determine correct, wafer thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Lessons learned from past wafer size transitions (5) showed that once the wafer thickness is specified it is difficult to change. Based on the simulation data (4,5), some data using sintered polysilicon 450 mm wafer and suppliers input, an initial thickness of 925 ± 25 µm was recommended as a good thickness for handling wafers. This is thicker than the extrapolated thickness trend from 125 mm to 300 mm wafers, as shown in Figure 2.…”
Section: Wafer Thickness Issuesmentioning
confidence: 99%
“…Lessons learned from past wafer size transitions (5) showed that once the wafer thickness is specified it is difficult to change. Based on the simulation data (4,5), some data using sintered polysilicon 450 mm wafer and suppliers input, an initial thickness of 925 ± 25 µm was recommended as a good thickness for handling wafers. This is thicker than the extrapolated thickness trend from 125 mm to 300 mm wafers, as shown in Figure 2.…”
Section: Wafer Thickness Issuesmentioning
confidence: 99%